Comparison of quadriceps Q-angle values of soccer players and wrestlers - Sen, M.; Çetin, S.; Ece, C.; Aydogan, A.; Çetin, H. N. (Journal of Education and Training Studies, 2019)
The aim of this study is to compare according to different positions the mean right and left knee Q angle of footballers and wrestlers. In this study, found the female soccer and wrestlers mean age 20.51 ± 3.47 years, height 165.43 ± 4.82 cm, weight 58.23 ± 5.18 kg. Male soccer and wrestlers has with mean age 21.30 ± 3.45 years, height 173.28 ± 5.45 cm, weight 65.66 ± 5.73 kg. One-way ANOVA, Student t, and Duncan post hoc test were used for statistical analysis. In this study, found that the mean right and left knee Q angles of male athletes were 15.08 ± 1.79° and 14.49 ± 1.82° for the standing position, 14.26 ± 1.84° and 13.29 ± 1.82° for the supine position.